Endometrioid adenofibroma of ovary-a two faced tumour: case report - Lucksom, Pesona G.; Kharka, Latha V.; Lepcha, Hissay; Rao, Sohan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Endometrioid variant of the adenofibromas accounts for only 1% of epithelial neoplasms of ovary. Though benign, specimen of endometroid adenofibroma of ovary needs to be evaluated by an experienced pathologist to rule out borderline and malignant cases. This prevents unnecessary adjuvant therapy for benign cases. We report a case of a large endometrioid adenofibroma arising at the left ovarian fossa in a post-menopausal woman who had undergone total abdominal hysterectomy with bilateral salpingo-oophorectomy 6 years back. Recurrence of endometroid adenofibroma of ovary is rare, however, long term follow-up is mandatory due to its low malignant potential. Though benign, specimen of endometroid adenofibroma of ovary needs to be evaluated by an experienced pathologist so that borderline and malignancy can be ruled out. Endometroid adenofibroma of ovary though benign needs long term follow up due to its low malignant potential.